2018
DOI: 10.1515/ntrev-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl cellulose-grafted graphene oxide for efficient antitumor drug delivery

Abstract: A drug delivery system based on carboxymethyl cellulose-grafted graphene oxide loaded by methotrexate (MTX/CMC-GO) with pH-sensitive and controlled drug-release properties was developed in this work. CMC was grafted on graphene oxide by ethylenediamine through hydrothermal treatment. CMC serves as a pH-sensitive trigger, while CMC-GO serves as a drug-carrying vehicle due to the curved layer and large plain surface. Different amounts of drugs could be loaded into CMC-GO nanocarriers by control of the original a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Surudžić et al [37] showed that synthetic polyvinyl alcohol/graphene (PVA/Gr) nanocomposites are good candidates for biomed-ical soft tissue implants and wound dressing. Jiao et al [38] found that polymers made by grafting carboxymethyl cel-lulose (CMC) to GO could be used as drug carriers. Wan et al [39] pointed out the potential of graphene and carbon-based nanomaterials as efficient adsorbents for oils and or-ganic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Surudžić et al [37] showed that synthetic polyvinyl alcohol/graphene (PVA/Gr) nanocomposites are good candidates for biomed-ical soft tissue implants and wound dressing. Jiao et al [38] found that polymers made by grafting carboxymethyl cel-lulose (CMC) to GO could be used as drug carriers. Wan et al [39] pointed out the potential of graphene and carbon-based nanomaterials as efficient adsorbents for oils and or-ganic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a single layer of carbon atoms with sp 2 chemical bonds, is the base for all nanoscale carbon materials such as fluorine bucky balls and carbon nanotubes (CNTs) [13][14][15][16][17][18][19][20]. Simple production procedures in comparison with other carbon nanomaterials and several properties, including zero band gap, high conductivity, flexibility, exceptional chemical stability, extremely wide porous structure, high specific surface area, high mobility of charge carriers and cost efficiency, make the graphene a promising nanomaterial for the next era [21].…”
Section: Introductionmentioning
confidence: 99%
“…GO has been widely used in medicine field owning to its large plain surface area which provides advantages for drug and protein delivery [4]. Jiao et al [5] loaded different amounts of drugs on carboxy-methyl cellulose-grafted graphene oxide, and high drug-loading efficiency and encapsulation efficiency were achieved, which could reach 39.33% and 29.50%. Innovative nano-drug (Ori@GE11-GO) was prepared to recognize the specific tumour cells, and improve anticancer efficiency [6].…”
Section: Introductionmentioning
confidence: 99%